Religious Moderation: Integrating Islamic Humanist Values in Building Human Existence According to the Perspective of Islamic Education - Wahib, Ahmad; Besari, Anam (Jurnal Paradigma, 2025)
This article aims to offer a solution and material for reflection and evaluation for every individualhuman being (especially muslims and Indonesian citizens) regarding the various differences that have become natural to God as the Creator., So the hope is to be able to become a person who has a relaxed, sincere and tolerant nature towards whatever things happen in each person's routine life. Literature review was chosen as a research method with a qualitative-descriptive approach in compiling the content of the discussion. The results of the research are: Islamic religious law from the past until now has always adhered to and provided freedom for every individual human being in life, equipped with certain references in its implementation. There are several efforts or steps offered towards Islamic humanist values such as emulating the noble qualities of Allah Swt (the Creator/God) in life., There is no application of sects or castes in any mosque because of equality of rank as servants of God's creation and the obligation to uphold justice based on Islamic religious law and the rules enforced in each region and need to have the will to analyze all forms of content of the teachings prescribed by the Islamic religion to be able to find ibrah or lessons from it. On the other hand, even if we look at Islamic education, of course these Islamic humanist values can indeed be said to be very much in line with the aims of universal Islamic education and in particular the formulation of Indonesian state education, which is oriented towards the realm of creed, worship and morals. Furthermore, regarding concrete manifestations in the reality of life, one of them can be applied as a basis in the realm of education and should be able to be packaged by collaborating with the nuances of custom or culture (local wisdom) of each region so that it has the implication of creating a more attractive impression and even maximizing the achievement of the desired goals, such as the example of the philosophical concept of “huma betang” in Central Kalimantan/the Dayak Ngaju tribe which carries three essential moral values, namely: a sense of kinship or familiarity with one another, a sense of togetherness or shared destiny and a sense of equality or equality of position as creatures created by God.